Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1088/1361-6528/ac0cb1
|View full text |Cite
|
Sign up to set email alerts
|

Validity of point-mass model in off-resonance dynamic atomic force microscopy

Abstract: The quantitative measurement of viscoelasticity of nano-scale entities is an important goal of nanotechnology research and there is considerable progress with advent of dynamic atomic force microscopy. The hydrodynamics of cantilever, the force sensor in AFM measurements, plays a pivotal role in quantitative estimates of nano-scale viscoelasticity. The point-mass (PM) model, wherein the AFM cantilever is approximated as a point-mass with mass-less spring is widely used in dynamic AFM analysis and its validity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Cantilever amplitude and phase difference between cantilever drive and actual oscillations at the tip are measured using an interferometer and recorded usina g lock-in amplifier. As shown in Figure 4 , phase difference is close to zero and featureless due to negligible contribution made by dissipation in off-resonance conditions [ 23 , 31 , 39 ]. However, amplitude signals show characteristic non-linear features every time a polymer is picked up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cantilever amplitude and phase difference between cantilever drive and actual oscillations at the tip are measured using an interferometer and recorded usina g lock-in amplifier. As shown in Figure 4 , phase difference is close to zero and featureless due to negligible contribution made by dissipation in off-resonance conditions [ 23 , 31 , 39 ]. However, amplitude signals show characteristic non-linear features every time a polymer is picked up.…”
Section: Resultsmentioning
confidence: 99%
“…This condition, therefore, forms a check on the correctness of our measurement. We have recently shown that for off-resonance operation, phase difference in the displacement signal z is 0 [ 23 , 31 ]. The amplitude signal gives the stiffness of the polymer molecule and both amplitude and phase are measured with a lock-in amplifier.…”
Section: Methodsmentioning
confidence: 99%
“…The point-mass model seems to be a gross oversimplification for a continuous beam oscillating in liquids; 65,77,84 however, it has been shown that it is adequate in certain experimental parameter space. 66 For a fixed separation of the base and the substrate, the above equation can also be written for z(t), the deviation of the tip from its equilibrium position.…”
Section: Cantilever Dynamics In a Viscous Mediummentioning
confidence: 99%
“…Typically, tip amplitude of 5 nm and cantilever stiffness of 0.1 N m À1 will exert a force modulation larger than 500 pN. 66,87 Due to these concerns, dynamic AFM measurements of proteins have been restricted to off-resonance operation. 88,89 It is also worthwhile to note that solution to eqn (10) is valid only when stiffness and damping coefficient are constant over the oscillation amplitude of the tip.…”
Section: Cantilever Dynamics In a Viscous Mediummentioning
confidence: 99%
See 1 more Smart Citation